Association between exposures to brominated trihalomethanes, hepatic injury and type II diabetes mellitus. (July 2016) - Makris, Konstantinos C.; Andrianou, Xanthi D.; Charisiadis, Pantelis; Burch, James B.; Seth, Ratanesh K.; Ioannou, Androniki; Picolos, Michael; Christophi, Costas A.; Chatterjee, Saurabh
Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered the most common liver disorder in the Western world, commonly diagnosed in the majority of obese patients with type 2 diabetes mellitus (T2DM). Metabolic disrupting chemicals with short half-lives, such as those of halogenated structure (trihalomethanes, THM) have been linked with hepatic insulin resistance phenomena in animal studies. However, human studies evaluating the role of THM exposure on liver pathogenesis and T2DM disease process are scarce. The objectives of this study were to: i) determine the association of urinary brominated THM (BrTHM) levels and T2DM disease status, and ii) investigate the association between urinary BrTHM levels and serum alanine aminotransferase (ALT) concentrations, often used as surrogate markers of NAFLD. A pilot case–control study was conducted in Nicosia, Cyprus (n = 95). Cases were physician-diagnosed T2DM patients and controls were healthy individuals. Liver enzymes, leptin and TNF-α were measured in sera, while urinary THM levels were measured using tandem mass spectrometry. Diabetics had higher levels of serum leptin, body mass index and ALT than the controls. Among all study participants those with serum ALT levels above the median (17 IU/L) had higher mean tribromomethane (TBM) concentrations compared to those with serum ALT below 17 IU/L. A significant increase in the odds of having above the median serum ALT levels [OR 6.38, 95% CI: 1.11, 42.84 (p = 0.044)] was observed for each unit increase in creatinine-unadjusted urinary TBM levels, along with BMI and past smoking, after adjusting for possible confounders, such as urinary creatinine, age, sex, and leptin; no other THM compound showed a significant association with serum ALT. Logistic regression models for T2DM using the urinary BrTHM as exposure variables did not reach the predetermined level of significance. The interplay between exposures to BrTHM and the initiation of key pathophysiological events relating to hepatic injury (ALT) and inflammation (leptin) was recognized via the use of selected biomarkers of effect. Our evidence that THM could act as hepatic toxins with a further initiation of diabetogenic effects call for additional studies to help us better understand the disease process of the two co-morbidities (NAFLD and T2DM). Graphical abstract: Conceptual representation of the association of brominated trihalomethanes (BrTHM) and type 2 diabetes mellitus (T2DM) in progressive nonalcoholic fatty liver disease (NAFLD) using data from the literature (predominantly animal studies) and also from this study: Overweight or obese status in mice exposed to BrTHM was characterized by insulin and leptin resistance patterns and linked with high levels of 4-hydroxynonenal (4-HNE) (Das et al., 2013 ). Mechanistically, BrTHM is metabolized by cytochrome P450 2E1 in microsomes of hepatocytes and form short-lived highly reactive di-halomethyl radicals. These radicals react with lipids (especially n-6-polyunsaturated fatty acids, PUFAs) causing lipid peroxidation (4-HNE release) and metabolic oxidative stress (Seth et al., 2013 ). 4HNE is a toxic reaction intermediate, altering both lipid and glucose metabolism. Further cumulative consequences of BrTHM metabolism and metabolic dysregulation potentiate inflammatory response in the liver, increasing serum alanine aminotransferase (ALT) levels (Seth et al., 2013 ); NAFLD may further progress to nonalcoholic steatohepatitis (NASH) or cirrhosis. Highlights: Preliminary evidence of trihalomethanes exposures and hepatic injury Higher leptin and hepatic injury markers in diabetics Elevated hepatic injury marker levels associated with higher bromoform levels